Play Behaviors in Children during the COVID-19 Pandemic: A Review of the Literature - Anastasia Kourti; Androniki Stavridou; Eleni Panagouli; Theodora Psaltopoulou; Maria Tsolia; Theodoros N. Sergentanis; Artemis Tsitsika (MDPI AG, 2021)
Play is a key factor for children's healthy psychological, emotional, social, and cognitive development. During the COVID-19 pandemic, it has been postulated that children's play was affected, not only regarding the time children spent playing but also in terms of the qualitative characteristics of play. The aim of this review was to investigate how children's play has changed during the COVID-19 pandemic. A review was conducted in the PubMed, Google Scholar, EMBASE, SCOPUS, ERIC, PsycInfo, and JSTOR databases up to 6 December 2020. Furthermore, references of eligible studies as well as of relevant articles were searched using a snowballing technique. The search retrieved 17 eligible studies, conducted in Europe and North America. In general, outdoor play was reduced during the pandemic; on the other hand, there was an increase in indoor play and in videogames-screen time. COVID-19 was present in children's pretend play. Children's play was a key contributor to children's mood and wellbeing. Furthermore, teachers were especially concerned about how children's play was affected during the lockdown measures. There is evidence that children's play habits were affected during the COVID-19 pandemic; further research is required, especially cross-culturally oriented.